Social determinants of health that impact the time to diagnosis and treatment of infertility in Taiwan - Wei-An Chen; Chia-Ling Wu; Hsin-Yi Ho; Fan Chang; Jehn-Hsiahn Yang; Fu-Tsai Kung; Ming-Jer Chen; Mei-Jou Chen (Journal of the Formosan Medical Association)
Background/purpose: Taiwan is one of the countries with the lowest birth rate in the world. We investigated factors associated with the time to diagnosis and treatment of infertility in Taiwan. Methods: The study was conducted through an online questionnaire in December 2021. The questionnaire was adapted from a previously published multinational survey, and culture-specific questions were added. 91 infertile patients and 89 partners of patients in Taiwan, aged 20- to 45- year-old, were included. Results: The average duration before diagnosis was 2.9 years, followed by 1.5 years before treatment. Older age at marriage (p = 0.0024), higher education level (P = 0.0001), and a higher gender equality score (p = 0.0031) were associated with earlier diagnosis. Conversely, folk therapy use was linked to later diagnosis (p < 0.0001) and treatment (p < 0.0001). Notably, in the female (p = 0.039) and patient (p = 0.0377) subgroups, a higher gender equality score was associated with a shorter duration of folk therapy. Subjectively, the most frequent factor influencing treatment decision was affordability or lack thereof. The government subsidy for in vitro fertilization led to increased treatment willingness for 46.3% of respondents, and 47.3% reported more likely to pursue earlier treatment. Conclusions: This study highlights the influence of education, gender equality, folk therapy, and government subsidy on fertility care decisions. To improve the timeliness of infertility healthcare in Taiwan, potential strategies include promoting education, fostering gender equality, providing financial support, and raising awareness on the association between folk therapy and delayed medical care.